PENGARUH PENGGUNAAN TEKNOLOGI SMART TV TERHADAP MOTIVASI BELAJAR SISWA PADA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS XI DI MADRASAH ALIYAH AL-ISLAM JAMSAREN SURAKARTA TAHUN 2025/2026 - Deliana Putri; Mukhlis Fathurrohman (Jurnal Manajemen Pendidikan, 2025)
This study aims to determine the level of Smart TV utilization in Islamic Cultural History (SKI) learning, the level of students’ learning motivation, and the effect of Smart TV use on the learning motivation of 11th-grade students at MA AL-Islam Jamsaren Surakarta in the 2025/2026 academic year. This research employed a quantitative approach with a survey method. The population consisted of 89 students, and a sample of 73 respondents was selected through simple random sampling. Data were collected using a Likert-scale questionnaire, validated and tested for reliability, and analyzed using simple linear regression with SPSS 25. The findings reveal that Smart TV utilization is categorized as high with an average score of 84.21, while students’ SKI learning motivation falls into the moderate-to-high category with an average score of 79.81. Regression analysis indicates a significant positive effect of Smart TV use on learning motivation, with a significance value of 0.000 (<0.05). The R Square value of 0.300 shows that Smart TV contributes 30% to the variation in learning motivation. The implication is that Smart TV serves as an effective learning medium to enhance SKI learning motivation through visual, audio, and interactive digital content. Schools and teachers are encouraged to continue optimizing this technology to create engaging and meaningful learning experiences.